Peningkatan Pemahaman terhadap Peran TNI dalam Pemberdayaan Masyarakat di Daerah Perbatasan Nusa Tenggara Timur - Posma Sariguna Johnson Kennedy (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2022)
The implementation of this community service activity is to conduct discussions aimed at increasing understanding of the duties of the TNI to assist local governments in community empowerment programs at the border of Nusa Tenggara Timur (NTT) Province. The method of writing this paper is to use a qualitative approach by reviewing various literature and discussions conducted with Korem 161/Wirasakti Kupang and Kodim 1605 Belu NTT. At the NTT border, the Border Security Task Force (Satgas Pamtas) 742/SWY TNI performs the main task of Border Security and explores the community's potential, and empowers this potential. There are many creations of this unit in "fighting poverty," namely through the five programs of the Wira Yudha House. Rumah Wira Yudha has programs in Education, Health, Love Pancasila, Entrepreneurship, and Wira Yudha Sharing to answer the needs and limitations in border villages. All these activities are full of activities based on Pancasila values.